Pemberdayaan Kelompok Perempuan Dalam Pembinaan Kewirausahaan di Kota Jayapura - Bleskadit, Novalia Herlina; Paru, Sara Marlyn (The Community Engagement Journal, 2024)
This community service activity aims to provide training to encourage women's empowerment and provide entrepreneurial opportunities in Jayapura City. The activity was carried out to assess the impact of community service programs related to women's empowerment and to evaluate existing entrepreneurial opportunities. The community service activity was carried out in women's empowerment groups in Jayapura City for 1 day, with predetermined criteria or considerations. The material discussed was the identification of entrepreneurial opportunities from the surrounding environment